2017
DOI: 10.1038/s41598-017-06375-w
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Matrix Protein, PfY2, Functions as a Crucial Macromolecule during Shell Formation

Abstract: Biomineralization, including shell formation, is dedicatedly regulated by matrix proteins. PfY2, a matrix protein detected in the ethylene diamine tetraacetic acid (EDTA)-soluble fraction from both prismatic layer and nacreous layer, was discovered by our group using microarray. It may play dual roles during biomineralization. However, the molecular mechanism is still unclear. In this research, we studied the function of PfY2 on crystallization in vivo and in vitro, revealing that it might be a negative regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
(63 reference statements)
2
19
0
Order By: Relevance
“…More studies are needed to elucidate this possibility. However, hemocytes in P. fucata could not be the main source of SMPs according to our results and previous studies 17 , 44 . Therefore we argued that, confined to provide calcium when necessary, hemocytes in oysters were unlikely to regulate the shell formation process solely, which was slightly different from a previous study 5 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…More studies are needed to elucidate this possibility. However, hemocytes in P. fucata could not be the main source of SMPs according to our results and previous studies 17 , 44 . Therefore we argued that, confined to provide calcium when necessary, hemocytes in oysters were unlikely to regulate the shell formation process solely, which was slightly different from a previous study 5 .…”
Section: Discussionsupporting
confidence: 86%
“…The collected hemocyte pellets and the mantle tissue (including the central part and the edge) were sampled for RNA extraction using TRIzol reagent (Invitrogen, Carlsbad, CA, USA) as described 44 . The concentration and quality of the purified RNA were determined by a Nanodrop 2000 spectrophotometer (Thermo Scientific, USA) and denaturing RNA electrophoresis in TAE agarose gels.…”
Section: Methodsmentioning
confidence: 99%
“…And the matrix proteins are proved to be involved in calcium carbonate nucleation, polymorphs selection, crystal orientation, and have been extensively studied (Liang et al, 2015; Miyamoto et al, 1996; Ponce and Evans, 2011; Takeuchi et al, 2008). It has been demonstrated that many matrix protein genes were upregulated after shell damage stimulation (Kong et al, 2009; Lin et al, 2014) and some SMPs have been proved to promote nucleation of calcium carbonate, such as PfY2 (Yan et al, 2017), Alv (Kong et al, 2018) and Prismalin-14 (Suzuki et al, 2004). Therefore, we speculate that the mantle tissue promotes the nucleation of calcium carbonate by secreting more organic matrix, thus accelerating the shell regeneration process.…”
Section: Resultsmentioning
confidence: 99%
“…Biomineralization is a complex, precise process regulated by multiple molecules 1,2 . However, recent studies have mainly focused on the functions of SMPs in shell biomineralization 8,[46][47][48] , leading to the lack of studies on the regulation of SMPs at upstream transcriptional level. miRNAs were found to regulate the gene expression post-transcriptionally in various biological processes 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Prisilkin-39 and ACCBP were of interest for further study because each of them was predicted to have a binding site with novel_miR_1 in the protein-coding sequence and they were well-studied as important participants in prismatic and nacreous layer formation respectively. Nacrein, detected in shell notching experiments in previous study 47 , was chosen as positive control. The expression of novel_miR_1 increased at 6 h after shell notching, reaching the peak at 24 h, and then decreased to the basal level in following hours (Fig.…”
Section: Discussionmentioning
confidence: 99%